1987
DOI: 10.1002/jca.2920030408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plateletpheresis on the fenwal CS‐3000 on donor platelet counts

Abstract: To evaluate the risk of significant plateletpheresis-induced thrombocytopenia in normal volunteer donors undergoing plateletpheresis less frequently than every 56 days and to help understand factors influencing platelet yield in these donors, pre- and postapheresis platelet counts (X 10(3)/microliter) and platelet yields were analyzed from 916 plateletpheresis procedures (Fenwal CS-3000) on 607 donors (405 men, 202 women). The mean preapheresis platelet count was 265 +/- 59 (SD) (range 155-650) (men 256 +/- 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
4
13
3
Order By: Relevance
“…Compared to results reported in the literature, our COM.TEC CE results (57 ± 15%) were similar to those reported: 52-55% [13,17,18]. However, our Amicus results (55 ± 15%) were lower than the reported averages of 66-73% [8][9][10][11][19][20][21][22]. On the other hand, when comparing the instruments with regard to PLT yield/blood volume processed, the Amicus showed a significantly higher ratio compared to the COM.TEC (0.42 vs. 0.33; p < 0.001).…”
Section: Discussioncontrasting
confidence: 54%
“…Compared to results reported in the literature, our COM.TEC CE results (57 ± 15%) were similar to those reported: 52-55% [13,17,18]. However, our Amicus results (55 ± 15%) were lower than the reported averages of 66-73% [8][9][10][11][19][20][21][22]. On the other hand, when comparing the instruments with regard to PLT yield/blood volume processed, the Amicus showed a significantly higher ratio compared to the COM.TEC (0.42 vs. 0.33; p < 0.001).…”
Section: Discussioncontrasting
confidence: 54%
“…found a 29.4% decrease in PLT count after donation, which was not clinically significant. [7] In the present study, five out of 237 donors (N = 5, Amicus) showed a post donation PLT ct of <100×10 9 /L (Range 80-100). All five donors had a pre donation PLT ct between 150-200×10 9 /L.…”
Section: Discussionsupporting
confidence: 46%
“…In 12% of the procedures, the mean yield was < 3 x 10 11 /unit when the pre-donation platelet count was < 200 x 10 3 /µl 4 . Many other studies have also demonstrated significant positive correlation between the donor platelet count and the yield of the product [10][11][12] .…”
Section: Discussionmentioning
confidence: 83%
“…Figure 1 shows a direct correlation between predonation platelet count and the platelet yield (r = 0.446, p < 0.001). The platelet count was > 3x 10 11 in 83% of procedures. Platelet yield was negatively correlated with MPV (r = -0.447) and PDW (r = -0.396) and was not found to be statistically significant as shown in Figure 2 and Figure 3 respectively.…”
Section: Resultsmentioning
confidence: 92%